The thinking strategist : unleashing the power of strategic management to identify, explore and solve problems - Edmondson, Vickie Cox (Emerald Publishing, 2022)
The Thinking Strategist promotes the strategic management process as a way to identify, explore and solve problems. It provides useful advice and practical tools to strengthen decision making and problem solving skills to accomplish organizational goals, exceed objectives, and to get top management and key stakeholder support.